Environmental Risk Related to the Exploration and Exploitation of Coalbed Methane - Barbara Uliasz-Misiak; Jacek Misiak; Joanna Lewandowska-Śmierzchalska; Rafał Matuła (Energies, 2020)
In coal seams, depending on the composition of coal macerals, rank of coal, burial history, and migration of thermogenic and/or biogenic gas. In one ton of coal 1 to 25 m3 of methane can be accumulated. Accumulation of this gas is included in unconventional deposits. Exploitation of methane from coal seams is carried out with wells from mining excavations (during mining operations), wells drilled to abandoned coal mines, and wells from the surface to unexploited coal seams. Due to the low permeability of the coal matrix, hydraulic fracturing is also commonly used. Operations related to exploration (drilling works) and exploitation of methane from coal seams were analyzed. The preliminary analysis of the environmental threats associated with the exploration and exploitation of coalbed methane has made it possible to identify types of risks that affect the environment in various ways. The environmental risks were estimated as the product of the probability weightings of adverse events occurring and weightings of consequences. Drilling operations and coalbed methane (CBM) exploitation leads to environmental risks, for which the risk category falls within the controlled and accepted range.